Behavioral Biases in the Crypto Market: Disposition, Herding, and Heuristic Effects on Investment Decisions - Putradia, Mikhael Kefas; Ratnawati, Kusuma (Jurnal Management Risiko dan Keuangan, 2025)
Purpose – This study aims to analyze the influence of disposition bias, herding bias, and heuristics on the investment decisions of cryptocurrency investors in Malang City.   Design/methodology/approach – This explanatory quantitative study uses primary data collected through online questionnaires distributed to 177 cryptocurrency investors domiciled in Malang City. The data were analyzed using Partial Least Squares (PLS) with SmartPLS to examine the relationships among behavioral bias variables and investment decisions.   Findings – The results show that disposition bias, herding bias, and heuristics significantly influence investment decisions. These findings indicate that psychological factors and behavioral biases play an important role in shaping investment decisions, particularly in the context of highly volatile cryptocurrency assets.   Originality/value  – This study contributes to behavioral finance literature by examining the role of cognitive and emotional biases in cryptocurrency investment decisions among young investors, providing insights for investors, industry participants, and regulators in developing appropriate financial education strategies.